2010
DOI: 10.1097/mrr.0b013e3283398198
|View full text |Cite
|
Sign up to set email alerts
|

Detecting changes following the provision of assistive devices: utility of the WHO-DAS II

Abstract: The World Health Organization Disability Assessment Schedule II (WHO-DAS II) is a non-disease-specific International Classification of Functioning, Disability, and Health-based disability assessment instrument developed to measure activity limitations and restrictions to participation. The aim of this pilot study is to evaluate WHO-DAS II responsiveness in detecting short-time changes following the provision of an Assistive Technology,which is important to define its utility in performing daily activities. Adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Its psychometric properties were confirmed in clinical samples (Garin et al, 2010), and proved to be responsive in detecting changes also after a short-term rehabilitation period (Chwastiak and von Korff, 2003;Raggi et al, 2010). Its psychometric properties were confirmed in clinical samples (Garin et al, 2010), and proved to be responsive in detecting changes also after a short-term rehabilitation period (Chwastiak and von Korff, 2003;Raggi et al, 2010).…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Its psychometric properties were confirmed in clinical samples (Garin et al, 2010), and proved to be responsive in detecting changes also after a short-term rehabilitation period (Chwastiak and von Korff, 2003;Raggi et al, 2010). Its psychometric properties were confirmed in clinical samples (Garin et al, 2010), and proved to be responsive in detecting changes also after a short-term rehabilitation period (Chwastiak and von Korff, 2003;Raggi et al, 2010).…”
Section: Methodsmentioning
confidence: 89%
“…There is a growing interest in obese patients' disability, generally described in terms of mobility limitations (Alley and Chang, 2007;Chen and Xuguang, 2008;Rejeski et al, 2008) and psychological distress (Atlantis and Baker, 2008;Bannon et al, 2009;Darby et al, 2009). Only one study described obese patients' disability features using an ICF-based approach (Raggi et al, 2010), highlighting moderate limitations in daily activities and a strong impact of body functions' impairments. Only one study described obese patients' disability features using an ICF-based approach (Raggi et al, 2010), highlighting moderate limitations in daily activities and a strong impact of body functions' impairments.…”
Section: Introductionmentioning
confidence: 99%
“…Kohler et al 16 wrote about core set development for people following amputation and two studies linked outcome measures to ICF. 5,6 Raggi et al 24 found the WHO-DAS II, an ICF-based disability instrument to be sensitive to the influence of assistive technology on person's functioning, but none of the included subjects had a prosthesis or orthosis.…”
Section: Introductionmentioning
confidence: 99%